MANUELA E.B. GIOLFO, FEDERICO SALVAGGIO (editors). 2023. More than Just Labels Relating TAFL to CEFR Levels. Roma: Aracne. 248 pp. ISBN: 979-12-218-1094-3 (Romano-arabica, 2025)
More than Just Labels Relating TAFL to CEFR Levels is a volume edited by Professors Giolfo and Salvaggio that brings together contributions from distinguished scholars with the aim to find answers and, more important, to raise awareness about the question of whether to relate the teaching of Arabic to European standards.